Madrasah ibtidaiyah NU Mathalibu ANALYSIS OF THE IMPLEMENTATION OF FULL DAY SCHOOLAT MI NU MATHALIBUL HUDA MLONGGO: A QUALITATIVE STUDY.: ANALYSIS OF THE IMPLEMENTATION OF FULL DAY SCHOOLAT MI NU MATHALIBUL HUDA MLONGGO: A QUALITATIVE STUDY. - David Adi Setyawan; Erna Zumrotun; Attalina, Syailin Nichla Choirin (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze the implementation of full day schoolat MI NU Mathalibul Huda Mlonggo, Mlonggo District, Jepara Regency using qualitative methods. The main focus of this study is to understand how the implementation of this program is implemented, what challenges are experienced, what are the effects on students and teachers, how teachers and students perceive the program, and what are the supporting and inhibiting aspects in its implementation. Information was collected through interviews, observations and documentation. The results of the study show that the implementation of full day schoolat MI NU Mathalibul Huda Mlonggo has had a positive impact on increasing academic achievement and student personality development. However, there are some challenges such as limited facilities and increased teacher workload. This study recommends the need for increased support for facilities and training for teachers to maximize the implementation of full day school.